⁷Be generation in the reaction of two-particle photodisintegration of ¹⁴N nucleus - Glaznev, M.S.; Gorbenko, E.S.; Bespalov, A.L.; Murtazin, R.T.; Khodyachikh, A.F. (Вопросы атомной науки и техники, 2014)
The reaction of two-particles nitrogen nucleus photodisintegration with ⁷Li and ⁷Be in the final state are investigated using diffusion chamber, which is placed into the magnetic field and filled with 15% nitrogen and helium compound. Chamber was irradiated with gamma rays from electron accelerator. The method of extraction of the reaction from the background two-particle reactions with multi-charged ions in the final state was created. Differential, full and integral cross-section of the reaction were measured. The results were compared with experimental data, where the full isotope ⁷Be output at ¹⁴N photodisintegration reaction was measured Реакция двухчастичного фоторасщепления ядра азота с выходом изотопов ⁷Li и ⁷Be исследована с помощью диффузионной камеры, заполненной 15% смесью азота с гелием и помещенной в магнитное поле. Камера облучалась тормозными γ-квантами от линейного ускорителя. Разработан метод выделения реакции из фоновых двухчастичных реакций с многозарядными ионами в конечном состоянии. Измерены дифференциальные, полные и интегральное сечения реакции. Проведено сравнение результатов с данными эксперимента, в котором измерен полный выход изотопа ⁷Be при фоторасщеплении ядра ¹⁴N . Реакцiю двочасткового фоторозщеплення азоту з виходом iзотопiв ⁷Li та ⁷Be дослiджено за допомогою дифузiйної камери, яку заповнено 15% сумiшшю азоту та гелiю i розмiщено у магнiтному полi. Камера опромiнювалася гальмiвними γ-квантами вiд лiнiйного прискорювача. Розроблено метод видiлення реакцiї з фонових двочасткових реакцiй з багатозарядними iонами в кiнцевому станi. Вимiряно диференцiйнi, повнi та iнтегральне перерiзи реакцiї. Проведено порiвняння результатiв з даними експерименту, в якому вимiряно повний вихiд iзотопу ⁷Be при фоторозщепленнi ядра ¹⁴N .